Postcard from Eugène Lemercier to his mother, Marguerite Lemercier, recalling his former freedom - Lemercier, Eugène Emmanuel, 1886-1915; Lemercier, Marguerite, 1859-ca. 1930 (1915)
Informs her that he finds the long monotonous days tiring and difficult to fill. Concludes : "it is now about true courage and true patience".
Addressed to "Madame Lemercier / 40 Rue Lauriston / Paris". No postmark.
There is an illustration in colours on the front of the postcard : three flags and two canons.
Keywords: Lemercier, Eugène Emmanuel, -- 1886-1915 -- Correspondence; World War, 1914-1918 -- France; World War, 1914-1918 -- France -- Correspondence; France -- History -- 1914-1940